2016
DOI: 10.1038/ncomms11861
|View full text |Cite
|
Sign up to set email alerts
|

Faster embryonic segmentation through elevated Delta-Notch signalling

Abstract: An important step in understanding biological rhythms is the control of period. A multicellular, rhythmic patterning system termed the segmentation clock is thought to govern the sequential production of the vertebrate embryo's body segments, the somites. Several genetic loss-of-function conditions, including the Delta-Notch intercellular signalling mutants, result in slower segmentation. Here, we generate DeltaD transgenic zebrafish lines with a range of copy numbers and correspondingly increased signalling l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 59 publications
4
63
0
Order By: Relevance
“…In mouse somitogenesis, the role of Notch signaling has been controversial: while blocking the pathway in embryos leads to the disappearance of Lfng oscillations (Barrantes et al, 1999; Ferjentsik et al, 2009), other studies reported that oscillations are maintained but desynchronized when Notch is inhibited (Okubo et al, 2012; Tsiairis and Aulehla, 2016). Notch1 and DLL1 oscillations could underlie the pulse dynamics (Bone et al, 2014; Kim et al, 2011; Liao et al, 2016; Shimojo and Kageyama, 2016). However, restoration of non-oscillatory expression of DLL1 in the mouse PSM leads to the formation of normal somites (Preusse et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse somitogenesis, the role of Notch signaling has been controversial: while blocking the pathway in embryos leads to the disappearance of Lfng oscillations (Barrantes et al, 1999; Ferjentsik et al, 2009), other studies reported that oscillations are maintained but desynchronized when Notch is inhibited (Okubo et al, 2012; Tsiairis and Aulehla, 2016). Notch1 and DLL1 oscillations could underlie the pulse dynamics (Bone et al, 2014; Kim et al, 2011; Liao et al, 2016; Shimojo and Kageyama, 2016). However, restoration of non-oscillatory expression of DLL1 in the mouse PSM leads to the formation of normal somites (Preusse et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, a 20% longer segmentation period was observed in the anterior somites in deltaD and mind bomb mutants and in DAPT-treated embryos (Herrgen et al., 2010). Conversely, the segmentation period could be shortened about 6.5% in transgenic line, Damascus , carrying multiple copies of deltaD-yfp (Liao et al., 2016). In zebrafish, more Notch signalling speeds the clock up, and less slows it down.…”
Section: A Three-tier Model Of the Segmentation Clockmentioning
confidence: 99%
“…As mentioned above in Section 3.2, the zebrafish Damascus transgenic line carries approximately 100 deltaD-venus / yfp transgene copies and showed higher Notch signalling strength and a faster segmentation rate in the embryo (Liao et al., 2016). The PSM length decreases at the same rate as in wildtype, but the anterior wavelength of the her1 gene expression waves in Damascus is about 20% shorter than in wildtype.…”
Section: Wave Patterns and Their Influence From Delta-notch Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies addressing the molecular mechanisms regulating the periodicity of clock gene oscillations have focused on the role of Notch signalling components [10,19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%